Delimitation of guava water productivity in the Brazilian northeast - De Teixeira, A. H.C.; Hernandez, F. B.T. (My University, 2012)
The intensification of agricultural crops in the Brazilian northeast results in a change of natural vegetation, making the quantification and evaluation of the additional water use important. Applications of a Geographic Information System (GIS) are presented in this paper to estimate the guava water productivity (GWP) on a large scale. Long-term weather data were used together with regression models involving crop coefficient (Kc), reference evapotranspiration (ET0) and accumulated degree days (DD ac) to quantify the guava water requirements (GWR) in the Brazilian Northeast producer states, considering an average growing season of six months and the cultivar 'Paluma' as a reference. By coupling GWR data with total precipitation for a growing season, it was possible to quantify the guava water deficit (GWD) giving an estimate about irrigation needs. Considering the whole region, the variation of the averaged GWD values ranged from 50 mm for pruning dates in January to 520 mm, with pruning done in May. Associating the average GWR values with yield data for 2010 from the Brazilian Geographical and Statistical Institute (IBGE), the average biophysical and economic values of GWP were estimated for each guava producer state. The biophysical values were between 0.86 and 4.95 kg m-3 for pruning dates in July and January in Rio Grande do Norte and Pernambuco states, respectively, while the economic ones ranged from 0.40 to 3.18 R$ m-3 for the same pruning periods, however, with the lowest averaged value being for Paraíba state. The states of Pernambuco, Bahia and Piauí presented the largest biophysical and economic GWP values. The spatially presented analyses can subsidize programs for the expansion of rainfed guava crop as well as water allocation criteria under irrigation conditions, aiming at improvements for water resource use. © ISHS.
Keywords: Crop coefficients; Degree days; Evapotranspiration; Water deficit; Water resources